Наука у XXI столітті: проблеми і перспективи - Онопрієнко, Ю.І. (№11, 2007)
The most actual science problem — correlation disturbance between scientific information accumulation and its interpretation opportunities — can be solved by creation of steady methodological frame of thinking — a general scientific methodology that can eliminate restrictions on the way of universal conceptual system building. It’s possible to overcome these obstacles by means of approaches that are based on universal (a priori by I. Kant) principles that define fundamental prosperities of the real world.